2018–2019 Florida Citrus Production Guide: Fresh Fruit Pesticide Residue Limits - Mark Ritenour (EDIS)
This 5-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Mark Ritenour and published by the Horticultural Sciences Department, May 2018.